Análise do game League of Legends sob o olhar da semiótica peirceana - NEGRÃO, Jéssyca Cristien Carvalho (2022)
The present work has as its object of study the sign game through the Peirceana semiotics approach, analyzed by the relation sign and its object. For that, it was chosen the game League of Legends from Riot Games. This work was based on the study of American semiotics, considering the League of Legends game as an objetc. Finally, present the contribution that the game League of Legends makes to semiotics.